On Spin-Statistics and Bogoliubov Transformations in Flat Spacetime With Acceleration Conditions - Good, Michael R.R. (My University, 2013)
A single real scalar field of spin zero obeying the Klein-Gordon equation in flat spacetime under external conditions is considered in the context of the spin-statistics connection. An imposed accelerated boundary on the field is made to become, in the far future, (1) asymptotically inertial and (2) asymptotically non-inertial (with an infinite acceleration). The constant acceleration Unruh effect is also considered. The systems involving non-trivial Bogoliubov transformations contain dynamics which point to commutation relations. Particles described by in-modes obey the same statistics as particles described by out-modes. It is found in the non-trivial systems that the spin-statistics connection can be manifest from the acceleration. The equation of motion for the boundary which forever emits thermal radiation is revealed
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; dynamical Casimir effect; Unruh effect; external conditions; moving mirrors